2020
DOI: 10.1111/rec.13139
|View full text |Cite
|
Sign up to set email alerts
|

Improving restoration success through microsite selection: an example with planting sagebrush seedlings after wildfire

Abstract: Post‐fire restoration of foundation plant species, particularly non‐sprouting shrubs, is critically needed in arid and semi‐arid rangeland, but is hampered by low success. Expensive and labor‐intensive methods, including planting seedlings, can improve restoration success. Prioritizing where these more intensive methods are applied may improve restoration efficiency. Shrubs in arid and semi‐arid environments can create resource islands under their canopies that may remain after fire. Seedlings planted post‐fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…If mountain big sagebrush does not establish well in the first couple of years after fire, sagebrush recovery is slow (Ziegenhagen and Miller 2009). Sagebrush also establishes better in microsites that are largely devoid of herbaceous vegetation Davies et al 2020). In our study, limited-to-no fire-induced mortality of perennial grasses resulted in few open spaces for establishment of sagebrush seedlings.…”
Section: Discussionmentioning
confidence: 56%
“…If mountain big sagebrush does not establish well in the first couple of years after fire, sagebrush recovery is slow (Ziegenhagen and Miller 2009). Sagebrush also establishes better in microsites that are largely devoid of herbaceous vegetation Davies et al 2020). In our study, limited-to-no fire-induced mortality of perennial grasses resulted in few open spaces for establishment of sagebrush seedlings.…”
Section: Discussionmentioning
confidence: 56%
“…We found that sufficient mortality occurred such that in unseeded and seeded areas, nearly half of the populations found to be occupied 1–2 years post‐fire were unoccupied 2–3 years post‐fire. Increased mortality of shrubs can be attributed to resource limitations, especially water (e.g., O'Connor et al, 2020), and increased competition with seeded non‐shrub species and non‐native species (Davies et al, 2020; Rinella et al, 2015). Within 3 years since sowing, aerial seeding of sagebrush either resulted in enough seedlings to reduce the likelihood of complete population mortality, or as mentioned previously, this apparent seeding effect may reflect manager decision‐making regarding which particular areas to restore.…”
Section: Discussionmentioning
confidence: 99%
“…We found that sufficient mortality occurred such that in unseeded and seeded areas, nearly half of the populations found to be occupied 1-2 years post-fire were unoccupied 2-3 years post-fire. Increased mortality of shrubs can be attributed to resource limitations, especially water (e.g., O'Connor et al, 2020), and increased competition with seeded nonshrub species and non-native species (Davies et al, 2020;Rinella et al, 2015). Within 3 years since sowing, aerial F I G U R E 6 Nonparametric multiplicative regression modeled relationships between sagebrush seedling occupancy rate (y-axis), native perennial grass cover (x-axis), and aerial sagebrush seeding status (colored line series; gray line is visible along x-axis; "+" indicates sagebrush seed applied, "À" indicates no sagebrush seed applied) in 103 populations sampled 1-2 years post-fire in areas with minimal fertile island microsite cover (0%-1.25%) and no remnant sagebrush plants detected within 150 m. This model was developed to simulate conditions where no mature sagebrush exited pre-fire.…”
Section: Seedling Prevalence Seeding Effect and Persistencementioning
confidence: 99%
See 2 more Smart Citations